2022
DOI: 10.11591/ijere.v11i3.22539
|View full text |Cite
|
Sign up to set email alerts
|

Madrasa teacher professionalism: Effects of gender and teaching experience in learning

Abstract: <span lang="EN-US">Developing professional madrasa teachers are increasingly popular in the classroom, but of these teachers, mixed results (without clear reasons) are reported. This article addresses the impact of gender and teaching experience (duration) on developing professional madrasa teachers, using the two factors as references. Research with a questionnaire was conducted in 75 public and private Aliyah Madrasas, with data collected from 325 teachers. Data analysis is differentiated based on madr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 45 publications
(84 reference statements)
0
2
0
Order By: Relevance
“…Various ways of assessing teacher teaching skill have been developed throughout the years (Zee & Koomen, 2016). In its shortened form, Tambak's Madrasa Teacher Teaching Skill Test (TMTT) was used in this study (Tambak et al, 2022). TMTT is made up of a stable factor structure that is broad enough to encompass a wide variety of relevant teacher abilities for instruction.…”
Section: Instrumentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Various ways of assessing teacher teaching skill have been developed throughout the years (Zee & Koomen, 2016). In its shortened form, Tambak's Madrasa Teacher Teaching Skill Test (TMTT) was used in this study (Tambak et al, 2022). TMTT is made up of a stable factor structure that is broad enough to encompass a wide variety of relevant teacher abilities for instruction.…”
Section: Instrumentsmentioning
confidence: 99%
“…So far, the learning practices conducted by madrasa teachers tend to be teacher-centered learning. Their instructional skills tend to be monotonous, using lecture methods and similar approaches (Efendi, 2021;Tambak et al, 2022). Madrasa teachers tend to teach without exploring their own abilities in order to produce excellent learning that is full of scholastic ability and creativity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the study draws attention to the potential influence of teaching experience on teacher competence and its subsequent impact on learning outcomes. Notably, teachers with less than 10 years of experience exhibit a broader spectrum of responses and understanding of the learning process (Tambak et al, 2022). This underscores the need for ongoing academic supervision to continually enhance teacher competence and foster an environment conducive to optimal differentiated learning practices.…”
Section: Introductionmentioning
confidence: 99%
“…The gender issue is not only in CT but also in many aspects of mathematics education studies (Putra, Hermita, Afrillia, et al, 2022;Putra, Hermita, Yuliani et al, 2022;Reilly et al, 2019;Tambak et al, 2022). According to Reilly et al (2019), a large-scale study (TIMSS results from 2011) on the investigation of gender differences in mathematics and sciences found that, while there were no general worldwide gender disparities, female students outperformed male students' mathematics and science proficiency among non-OECD countries.…”
Section: Introductionmentioning
confidence: 99%